Clinicopathological Features of Gestational Trophoblastic Neoplasia (GTN): Single Institutional Study - Jawad Ali Memon, Mohammad Sibtain Shah, Zubair Ali Memon, Abdul Rashid Baloch, Saeeda Bano, Noor Mustafa (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The term "gestational trophoblastic neoplasia" (GTN) refers to abnormal proliferation of trophoblastic tissue and occurs during pregnancy. It includes hydatiform mole, invasive mole, choriocarcinoma, placental site trophoblastic tumour and epitheliod trophoblastic tumour. Patients and Methods: This retrospective study was conducted at the Department of radiology, Peoples Medical College, Hospital, Nawabshah, Shaheed Benazirabad, Sindh; the clinical & ultrasonographic records of biopsy-proven cases of gestational trophoblastic disease registered in the department from January 1, 2019, to December 31, 2020 was evaluated and analysed through SPSS. Results: Total of 137 patients of biopsy proven gestational trophoblastic tumor was registered during the period. The age of the patient ranges between 15 to 50 years, the disease is most common in 21 to 30 years of age. Majority of patients belong to the rural areas (73%) in comparsion to urban area (26%).The most common tumor was hydatiform mole (76% ) followed by choriocarcinoma Conclusion: Gestational trophoblastic neoplasia are common disease in females of 21 to 30 years of age and hydatiform mole is the most frequent tumor type Keywords: Gestational trophoblastic disease, Hydatiform Mole, Malignancy, Ultrasound.